Cobalt-substituted Ba0.8Ca0.2Fe12O19 ceramics for wide-bandwidth microwave absorption within 2.6–18 GHz. Issue 17 (1st December 2019) - Feng, Gangli; Zhou, Wancheng; Li, Yiwen; Qing, Yuchang; Duan, Shichang; Jia, Hongyao; Luo, Fa; Zhu, Dongmei; Huang, Zhibin; Zhou, Yingying
Abstract: The electromagnetic properties of Ba0.8 Ca0.2 Fe12- x Co x O19 (BCFCO, x = 0.0, 0.6, 0.8, 1.0 and 1.2) ceramics prepared by pressureless sintering were investigated within 2.6–18 GHz. The Co 3+ -substituted ceramics show the influence of the Co 3+ ions enhanced the complex permeability as compared to the without Co 3+ ions. The magnetic resonance behavior of BCFCO ceramics mainly depends on the Co 3+ content, and the μ - f spectra show enhanced resonance absorption peaks when x increases from 0.6 to 0.8. A refection loss exceeding −5 dB (68.4% absorption) can be obtained in frequency range of 6.0–18 GHz for the Ba0.8 Ca0.2 Fe11.2 Co0.8 O19 ceramics with a thickness of 1.5 mm. This suggests that the Ba0.8 Ca0.2 Fe11.2 Co0.8 O19 ceramic can be used as an effective microwave absorber with a wide bandwidth.